2004
DOI: 10.1111/j.0269-8463.2004.00854.x
|View full text |Cite
|
Sign up to set email alerts
|

Transgenerational plasticity for sexual reproduction and diapause in the life cycle of monogonont rotifers: intraclonal, intraspecific and interspecific variation in the response to crowding

Abstract: Summary 1.In monogonont rotifers parthenogenetic reproduction allows population growth, and mictic (sexual) reproduction leads to the production of diapausing eggs. When amictic females are exposed to a mixis stimulus, they produce mictic daughters, whose eggs develop into males or, if fertilized, into diapausing eggs. Experiments showed that mictic offspring production is initiated by crowding in females of angularis , E. senta and R. frontalis , the propensity of amictic females to respond to crowding by pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
67
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(76 citation statements)
references
References 29 publications
9
67
0
Order By: Relevance
“…Although Gilbert provided stimuli large enough to induce mixis, these females continued to reproduce asexually, and only after several generations responded to the mixis stimulus. This transgenerational effect has been demonstrated in other rotifer species as well (Schroder and Gilbert 2004), although it has yet to be tested in B. plicatilis. Nevertheless, if delayed mixis exists in B. plicatilis, it could provide a mechanism to prevent a low-abundance species having just emerged from resting eggs from being induced by a highly abundant co-occurring species.…”
Section: Discussionmentioning
confidence: 95%
“…Although Gilbert provided stimuli large enough to induce mixis, these females continued to reproduce asexually, and only after several generations responded to the mixis stimulus. This transgenerational effect has been demonstrated in other rotifer species as well (Schroder and Gilbert 2004), although it has yet to be tested in B. plicatilis. Nevertheless, if delayed mixis exists in B. plicatilis, it could provide a mechanism to prevent a low-abundance species having just emerged from resting eggs from being induced by a highly abundant co-occurring species.…”
Section: Discussionmentioning
confidence: 95%
“…This study reaches up to Category II a , as it does not hold an among-population comparison. Additionally, several other empirical studies have reported variability in the timing of sex among rotifer populations of different species and from different habitats (Category II b ; Schröder & Gilbert, 2004;Gabaldón & Carmona, 2015), but they fail to look at the match between this variability and the degree of environmental unpredictability. We conclude that evidence for bet hedging in the timing of sex is still weak, likely because of several reasons: (1) many studies often lack accurate measurements for habitat predictability-due to the fact that appropriate metrics for the organism on focus and long-term monitoring are required (García-Roger et al 2014), (2) confounding effects such as the possible relationship between growing season length and predictability are not dissected (e.g.…”
Section: The Timing Of Sexmentioning
confidence: 99%
“…The timing of sex has been proposed as an instance of the conservative bet-hedging trait in rotifer populations inhabiting unpredictable environments (Carmona et al, 1995;Serra & King, 1999;Schröder & Gilbert, 2004;Serra et al, 2004;Gilbert, 2007a). If the end of the growing season-or the nutritional conditions required for diapausing egg production (Gilbert, 2010)-cannot be predicted by rotifers, then producing diapausing eggs as soon as possible can avoid the risk of a zero-fitness event.…”
Section: The Timing Of Sexmentioning
confidence: 99%
See 2 more Smart Citations